Improvement of microstructure of bovine hydroxyapatite with yttria - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2007)
Composites of calcinated bovine bone derived hydroxyapatite (HA) with 0.5 and 1 wt% Y2O3 were prepared by sintering. Money and time saving feature the production of HA from natural sources. In this study, results of scanning electron microscopy (SEM) and X-ray diffraction analysis aimed to interpret the results of measurements of clensification, microhardness, and compression strength of the produced composites. The best mechanical properties were achieved after sintering at 1200 degrees C for compressive strength and 1300 degrees C for microhardness. The results are in a fair agreement with densification measurements and microstructure analysis.
Keywords: hydroxyapatite; yttria; sintering; microstructure; mechanical properties; MECHANICAL-PROPERTIES; COMPOSITES